Expanding the environment: gene × school‐level SES interaction on reading comprehension. (1st June 2013) - Hart, Sara A.; Soden, Brooke; Johnson, Wendy; Schatschneider, Christopher; Taylor, Jeanette
Abstract : Background: Influential work has explored the role of family socioeconomic status (SES) as an environmental moderator of genetic and environmental influences on cognitive outcomes. This work has provided evidence that socioeconomic circumstances differentially impact the heritability of cognitive abilities, generally supporting the bioecological model in that genetic influences are greater at higher levels of family SES. The present work expanded consideration of the environment, using school‐level SES as a moderator of reading comprehension. Methods: The sample included 577 pairs of twins from the Florida Twin Project on Reading, Behavior and Environment. Reading comprehension was measured by the Florida Comprehensive Achievement Test (FCAT) Reading in third or fourth grade. School‐level SES was measured by the mean Free and Reduced Lunch Status (FRLS) of the schoolmates of the twins. Results: The best‐fitting univariate G × E moderation model indicated greater genetic influences on reading comprehension when fewer schoolmates qualified for FRLS (i.e., 'higher' school‐level SES). There was also an indication of moderation of the shared environment; there were greater shared environmental influences on reading comprehension at higher school‐level SES. Conclusions: The results supported the bioecological model; greater genetic variance was found in school environments in which student populations experienced less poverty. In general, 'higher' school‐level SES allowed genetic and probably shared environmental variance to contribute as sources of individual differences in reading comprehension outcomes. Poverty suppresses these influences.